An Empirical Model of Labor Supply in a Life-Cycle Setting - MaCurdy, Thomas E. (Journal of Political Economy, 1981)
This paper formulates and estimates a structural intertemporal model of labor supply. Using theoretical characterizations derived from an economic model of lifetime behavior, a two-step empirical analysis yields estimates of intertemporal and uncompensated substitution effects which provide the information needed to predict the response of hours of work to life-cycle wage growth and shifts in the lifetime wage path.